2021
DOI: 10.1007/s11695-021-05493-9
|View full text |Cite
|
Sign up to set email alerts
|

30-Day Morbidity and Mortality of Bariatric Surgery During the COVID-19 Pandemic: a Multinational Cohort Study of 7704 Patients from 42 Countries

Abstract: Background There are data on the safety of cancer surgery and the efficacy of preventive strategies on the prevention of postoperative symptomatic COVID-19 in these patients. But there is little such data for any elective surgery. The main objectives of this study were to examine the safety of bariatric surgery (BS) during the coronavirus disease 2019 (COVID-19) pandemic and to determine the efficacy of perioperative COVID-19 protective strategies on postoperative symptomatic COVID-19 rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 39 publications
0
22
1
Order By: Relevance
“…Half of centers provided FFP3/N95 masks in the operation room and staff-screening was performed in third of hospitals. They found same complication rate during the pandemic and concluded it is safe to continue surgery care using preventive protocols (38).…”
Section: Discussionmentioning
confidence: 92%
“…Half of centers provided FFP3/N95 masks in the operation room and staff-screening was performed in third of hospitals. They found same complication rate during the pandemic and concluded it is safe to continue surgery care using preventive protocols (38).…”
Section: Discussionmentioning
confidence: 92%
“…The data obtained in the GENEVA study were further complemented by a multinational cohort comprising 7704 patients analyzed between May and October 2020 [ 16 ]. Of the total number of patients, 43 (0.56%) had symptomatic COVID-19 in the first 30 days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these patients had surgical complications Clavien-Dindo I (67.4%) or II (25.6%), which may be due to the longer postoperative hospital stay. The study reported only one death related to COVID-19 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 'Global 30-day outcomes after bariatric surgery during the COVID-19 pandemic' (GENEVA) showed that bariatric and metabolic surgery could be performed safely during the pandemic [39]. The complete dataset from this study has been reported recently for adults and adolescents [77,78]. In this study, 499 surgeons from 185 centres in 42 countries provided complete data on 7704 patients.…”
Section: Outcomes In Patients Undergoing Elective Benign Surgery During the Covid-19 Pandemicmentioning
confidence: 95%